Rhizosphere wettability decreases with root age: a problem or a strategy to increase water uptake of young roots? - Carminati, Andrea (Frontiers in Plant Science, 2013)
As plant roots take up water and the soil dries, water depletion is expected to occur in the vicinity of roots, the so called rhizosphere. However, recent experiments showed that the rhizosphere of lupines was wetter than the bulk soil during the drying period. Surprisingly, the rhizosphere remained temporarily dry after irrigation. Such water dynamics in the rhizosphere can be explained by the drying/wetting dynamics of mucilage exuded by roots. The capacity of mucilage to hold large volumes of water at negative water potential may favor root water uptake. However, mucilage hydrophobicity after drying may temporarily limit the local water uptake after irrigation. The effects of such rhizosphere dynamics are not yet understood. In particular, it is not known how the rhizosphere dynamics vary along roots and as a function of soil water content. My hypothesis was that the rewetting rate of the rhizosphere is primarily function of root age. Neutron radiography was used to monitor how the rhizosphere water dynamics vary along the root systems of lupines during drying/wetting cycles of different duration. The radiographs showed a fast and almost immediate rewetting of the rhizosphere of the distal root segments, in contrast to a slow rewetting of the rhizosphere of the proximal segments. The rewetting rate of the rhizosphere was not function of the water content before irrigation, but it was function of time. It is concluded that rhizosphere hydrophobicity is not uniform along roots, but it covers only the older and proximal root segments, while the young root segments are hydraulically well connected to the soil. I included these rhizosphere dynamics in a microscopic model of root water uptake. In the model, the relation between water content and water potential in the rhizosphere is not unique and it varies over time, and the rewetting rate of the rhizosphere decreases with time. The rhisosphere variability seems an optimal adaptation strategy to increase the water upt